Haemato-biochemical changes in mis-mated pregnant dogs treated for termination of pregnancy - Keerthana Komalan; B. Bibin Becha; C. Jayakumar; Shibu Simon; R.S. Abhilash; S.S. Devi (Journal of Veterinary and Animal Sciences, 2025)
Study was conducted to compare the efficacy of mifepristone alone or in combination with cabergoline for termination of unwanted pregnancy in different stages of gestation in dogs by haemato-biochemical evaluation. Twentyfour pregnant dogs with a history of misalliance were divided into two groups: Group I consisting of dogs between 30 and 35 days of gestation, and Group II with dogs over 35 days of gestation. Each group was further divided into two subgroups: subgroup a, which was treated with mifepristone alone, and subgroup b, which received both mifepristone and cabergoline. Haemato-biochemical parameters were studied on the day of presentation, day 6 and day 11.On haematology, no significant difference was observed in TEC, Hb, VPRC, platelet count, MCV, MCH and MCHC between the days of observation within and between groups. The dogs, on different observation days, exhibited a mean total TLC at the upper limit of the normal range. On day 6, mean TLC increased in Group I and decreased in Group II. Serum BUN, creatinine and ALP levels were within normal range on all days of observations, there was no significant difference between the days of observation within and between the groups. Decline in ALP levels over time in all dogs, suggesting that a portion of ALP production by foetuses. Based on haemato-biochemical analysis on different days of observation, treatments using mifepristone alone or in combination with cabergoline was found to be effective in termination of pregnancy during mid gestation and after mid gestation.